E-commerce Strategies in Fashion : Exploring the Correlation Between Psychological Pricing Techniques and Customer Satisfaction in the context of Impulsive Online Buying Behavior - Singh, Shubhangi; Miklánek, Tomáš; Sáenz de Viteri Vázquez, Andrea; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
In the fluctuating market of digital commerce, particularly in the fashion sector, psychological pricing has risen to become one of the powerful methods through which consumer behaviour is manipulated. This study tries to determine the ways in which charm prices, both subtle and overt, urgency cues ("Only a few left!"), countdown timers, and promotional bundling ("Buy 2, Get 1 Free") may stimulate the impulse buying tendency among internet shoppers. Based on behavioural economic theories such as the scarcity principle and prospect theory, the study aimed to observe how these pricing strategies influence immediate purchase decisions and post-purchase evaluation. Using primary data from 150 respondents via a structured questionnaire, the study used correlation analysis to examine the relationships between emotional stimuli and impulsive buying behaviours. The results provided evidence that psychological-price strategies have a very close and statistically significant relationship with impulse purchase behaviour. Respondents perceived urgency cues and time-limited offers, which often led to spontaneous purchasing. Yet, some participants came to feel less satisfied after their purchase because of this short-term gratification and when the value was incommensurate with their initial expectations. Based on the findings, key recommendations can be made by this study. In the attempt to nurture long-term consumer trust, e-commerce companies should consider ethical and transparent pricing policies. Emergency marketing tactics may improve sales, but if applied to an extreme, they may lose the trust of the consumers. Consumers should be aware that it is an emotional trigger and a necessary evaluation before acting on the promotional cue. Besides, consumer education in terms of digital literacy would better arm consumers with price consciousness.
The study has major managerial implications, and it suggests that sustainable success in e-commerce is hotly debated and goes beyond the persuasive pricing method. A firm that respects the intelligence of its consumers and the need to engage them with honesty will be able to create a loyal customer base in a fast-heating, competitive environment.
Vedoucí práce: Tomáš Miklánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses